Orthodontic Management of a Severely Rotated Maxillary Central Incisor in the Mixed Dentition: A Case Report - Arezoo Jahanbin (Journal of Dental Materials and Techniques, 2014)
The aim of this case report was to introduce an appliance for correcting severe rotation of anterior teeth in the mixed dentition period. A 9-year-old Iranian boy with a mixed dentition Class I malocclusion complained of a severely rotated of upper right central incisor. There was a mesiodens between the central incisors. The supernumerary tooth was first extracted and then a Whip appliance which is composed of a removable plate, a cantilever spring and a central bracket on the rotated tooth was utilized. After 8 months, the upper right central incisor was orthodontically brought into proper alignment. Circumferential supracrestal fibrotomy was performed on the overcorrected tooth. One week after surgery, the device was removed and the retention was started. The whip appliance is a removable appliance that can effectively correct severe rotation of anterior teeth especially during the mixed dentition period.